When a rare condition creates a scientific society: The history of the International Society for Placenta Accreta Spectrum (IS-PAS) - Chantraine, F; Stefanovic, V; Braun, T; Calda, P; Martinelli, P; Collins, S (Wiley, 2021)
Almost 10 years ago, clinicians at multiple locations all over Europe observed an increased number of antenatally undiagnosed cases of placenta accreta spectrum (PAS) resulting in significant morbidity and the occasional maternal death. But even with an improvement in the antenatal imaging, the management of severe PAS remains challenging. One solution to improve understanding in rare but potentially lethal conditions is international collaboration. Consequently, a European working group was formed which over the next few years grew into an international society, the IS-PAS. The collective goals are to develop a large shared database of cases, generate high quality research into all aspects of PAS and improve education of both healthcare professionals and patients. The first results of this collaboration are presented within this supplement.